1996
DOI: 10.1128/mcb.16.4.1450
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interactions of Phosphatidylinositol 3-Kinase with GTPase-Activating Protein in 3T3-L1 Adipocytes

Abstract: The role of phosphatidylinositol (PI) 3-kinase in specific aspects of insulin signaling was explored in 3T3-L1 adipocytes. Inhibition of PI 3-kinase activity by LY294002 or wortmannin significantly enhanced basal and insulin-stimulated GTPase-activating protein (GAP) activity in 3T3-L1 adipocytes. Furthermore, removal of the inhibitory influence of PI 3-kinase on GAP resulted in dose-dependent decreases in the ability of insulin to stimulate p21ras. This effect was specific to adipocytes, as inhibition of PI 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 68 publications
2
22
0
Order By: Relevance
“…This controversial finding might be explained by tissue-specific differences in interactions of signalling molecules (6). In 3T3-L1 adipocytes, the PI3K inhibitor LY294002 blocks activation of p21 ras and decreases MAP kinase activation by insulin (6). However, we do not see MAP kinase activation by increased PI3K activity alone, suggesting that other signalling events need to be stimulated in parallel.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This controversial finding might be explained by tissue-specific differences in interactions of signalling molecules (6). In 3T3-L1 adipocytes, the PI3K inhibitor LY294002 blocks activation of p21 ras and decreases MAP kinase activation by insulin (6). However, we do not see MAP kinase activation by increased PI3K activity alone, suggesting that other signalling events need to be stimulated in parallel.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, activated PI3K was found not to affect MAP kinase activation in COS-7 cells (21). Indeed, the activation of PI3K might have a more permissive role for p21 ras activation by functional interaction with the GTPase-activating protein in 3T3-L1 adipocytes (6).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies have in fact shown that p85 can be recruited to tyrosine-phosphorylated proteins independent of p110 (41). Other studies have demonstrated that p85 is able to couple to p120 Gap and Grb2 (42,43), proteins involved in the regulation of Ras activation. As carbachol has been shown to activate Ras in other cell systems (44), it is possible that calcium agonists activate the Ras pathway via coupling to p85.…”
Section: Effect Of Wortmannin On Calcium-dependent Chloride Secretionmentioning
confidence: 98%
“…RasGAP also binds the Src-related family of kinases, including Src, Hck, Fyn, and Lck, through its Nterminal proline-rich region, serving as a substrate for these kinases (17). It binds Rab5 and stimulates its activity (18), whereas, it co-precipitates with p85 phosphatidylinositol 3-kinase, which inhibits its activity (19). It binds annexin VI through its C2, Ca 2ϩ -dependent, lipid-binding domain (20), the significance of which is still unknown.…”
mentioning
confidence: 99%